Karakteristik Konsep Diri Berdasarkan Jenis Kelamin - Halisa Tri Agustin; Cucu Arumsari; Agung Nugraha (Conseils : Jurnal Bimbingan dan Konseling Islam, 2026)
This study aims to describe the characteristics of students’ self-concept based on gender differences. The research employed a quantitative descriptive design with a total of 206 students from the Faculty of Teacher Training and Education as participants. The self-concept instrument used consisted of categorical scoring, producing four levels: very low, low, high, and very high. Data were analyzed using descriptive statistics to compare the distribution of categories between male and female students. The results show that both male and female students predominantly fall into the high and very high categories. Female students demonstrate a more stable and mature self-concept profile, indicated by the dominant proportion in the very high category (51.39%) and the absence of students in the very low category. Male students also show strong self-concept characteristics, with 50% in the very high category, although variations appear in the lower categories. These findings indicate that gender differences contribute to variations in self-concept formation and stability.